Posterior midgut epithelial cells differ in their organization of the membrane skeleton from other Drosophila epithelia. - Baumann, O. (Experimental Cell Research, 2001)
In epithelial cells, the various components of the membrane skeleton are segregated within specialized subregions of the plasma membrane, thus contributing to the development and stabilization of cell surface polarity. It has previously been shown that, in various Drosophila epithelia, the membrane skeleton components ankyrin and alphabeta-spectrin reside at the lateral surface, whereas alphabeta(H)-spectrin is restricted to the apical domain. By use of confocal immunofluorescence microscopy, the present study characterizes the membrane skeleton of epithelial cells in the posterior midgut, leading to a number of unexpected results. First, ankyrin and alphabeta-spectrin are not detected on the entire lateral surface but appear to be restricted to the apicolateral area, codistributing with fasciclin III at smooth septate junctions. The presumptive ankyrin-binding proteins neuroglian and Na(+),K(+)-ATPase, however, do not colocalize with ankyrin. Second, alphabeta(H)-spectrin is enriched at the apical domain but is also present in lower amounts on the entire lateral surface, colocalizing apicolaterally with ankyrin/alphabeta-spectrin. Finally, despite the absence of zonulae adherentes, F-actin, beta(H)-spectrin, and nonmuscle myosin-II are enriched in the midlateral region. Thus, the model established for the organization of the membrane skeleton in Drosophila epithelia does not hold for the posterior midgut, and there is quite some variability between the different epithelia with respect to the organization of the membrane skeleton.